Electromagnetic Field Evaluation of a 500kV High Voltage Overhead Line - Shadreck Mpanga; Wang Feng; Chen Chun (Institute of Advanced Engineering and Science, 2013)
Many scientific articles have been written about electromagnetic field distributions under high voltage overhead transmission lines. However, some readers are still left wondering just how exactly the distribution curves formed by the fields are related to the mathematical models used. This paper presents case study results of a 500 kV alternating current overhead transmission line, and explicitly shows how the fields vary under high voltage lines by employing easily understood mathematical models. The numerical simulations, done using MATLAB, can help anyone willing to evaluate the amount of electromagnetic fields available under any other high voltage overhead transmission line. The magnitudes of the fields obtained are compared with the standard values set by the International Radiation Protection Agency so as to assess the integrity of external insulation of the line. Thus, the technical staff can easily attend to complaints that may arise about the electromagnetic field effects from the line. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2007